Lipase-catalysed deacetylation of androstane and pregnane derivatives: Influence of ring D substitution - Bruttomesso, Andrea; Baldessari, Alicia (Journal of Molecular Catalysis B: Enzymatic)
A series of acetoxy derivatives of androstane and pregnane was deacetylated in organic solvents by microbial lipases. The best results were obtained with lipase from Candida antarctica (CAL B), Candida rugosa (CRL) and Pseudomonas sp. (PSL). In some derivatives, CAL B and CRL showed a regioselective behaviour towards the removal of the 3β- or 16α/16β-acetyl group. The results of the enzymatic deacetylation of pregnanes and androstanes substituted by various groups containing an sp2-hybridised C-atom in ring D could suggest that CAL B activity seems to be conditioned by the occurrence of a polar carbon double bond in this part of the steroid skeleton. Ten new steroid derivatives were obtained through this approach. Fil: Bruttomesso, Andrea. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Orgánica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina Fil: Baldessari, Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Orgánica; Argentina